Mannitol Production from Fructose by Using Resting Cells of Methylotrophic Yeasts - Nisa Yulianti Suprahman; Khairul Basyar; Herman Suryadi (Universitas Airlangga, 2022)
Background: Mannitol is a polyol sugar widely used in pharmaceutical and food industries which can be produced by bioconversion. Using of resting cells and methanol as a carbon source are strategies to increase the efficiency of mannitol production by increasing NAD(P)H needed in the reduction process. Objectives: This research aimed to optimize bioconversion condition by using resting cells of methylotrophic yeasts with methanol and fructose as carbon source and substrate, respectively. Methods: Several isolates were used including Candida sp, Debaryomyces nepalensis and Debaryomyces hansenii and three species suspected to be yeast isolated from a local paddy field. The methylotrophic characteristic of the yeasts was screened by turbidometry. The optimization of fermentation condition was conducted by varying cultivation time (24-96 hours), resting cell concentration (30-140 mg/mL), fructose concentration (7.5-15%), ammonium sulphate concentration (0.25-0.75%) and aeration condition (50-80%). Quantitative analysis of the mannitol was conducted by HPLC with NH2 column and Refractive Index Detector. Results: D. hansenii showed the highest yield value in mannitol production (23.17%), followed by D. nepalensis, Isolate A and Candida sp. (6.52%, 6.50% and 4.38%, respectively). Variation of bioconversion condition using D. hansenii showed that the highest resting cell concentration (140 mg/mL) incubated for 72 hours, moderate fructose concentration (10%), the highest ammonium sulphate concentration (0.75%) and moderate aeration condition (70%) would result in the highest yield value of mannitol (60%). Conclusion: This finding showed the potency of D. hansenii in mannitol production and gave preliminary information of its optimum fermentation condition.